Characterization of the adaptive immune responses in enterovirus a71 infection / Aw Yong Kam Leng - Aw, Yong Kam Leng (2016)
Hand, foot and mouth disease (HFMD) is a common childhood disease caused by many enteroviruses, including enterovirus A71 (EV-A71). Understanding the adaptive immune responses in EV-A71 infection is critical for the development of diagnostic tools, and potential therapeutics and vaccines. The first objective of the study was to determine the antibody responses in HFMD patients. EV-A71-specific IgM antibodies in serum samples from 89 patients with HFMD were detected by commercial IgMcapture enzyme-linked immunosorbent assay (ELISA) and IgM-colloidal gold immunochromatographic assay (GICA). The sensitivity, specificity, positive predictive value, and negative predictive value rates were 78.4, 80.8, 74.4, and 84.0%, respectively, for the IgM-capture ELISA, and 75.7, 76.9, 70.0, and 81.6% for the IgM GICA. Concordance between the two assays was 91.1%. The overall performance suggests that both commercial diagnostic kits are suitable for early diagnosis of HFMD caused by EV-A71 in Malaysia. For the second objective, these sera were subsequently used to characterize antibody responses against the structural and non-structural proteins of EVA71. Each viral protein was cloned and expressed in either bacterial or mammalian systems, and tested with antisera by Western bloting. The results revealed that all structural proteins (VP1-4), and non-structural proteins 2A, 3C and 3D were targets of EV-A71 IgM, whereas EV-A71 IgG recognized all the structural and non-structural proteins. Subsequent characterization of linear B-cell epitopes on EV-A71 was performed with 63 biotinylated peptides predicted to be immunogenic in silico. In total, 22 IgM and 4 IgG dominant linear epitopes were identified. The amino acid sequences of these epitopes were then aligned with 12 enterovirus species, and peptides were further tested with individual serum and mapped to their structural localization. PEP27 (VP1 142-156) and PEP23 (VP1 41-55) were identified as EV-A71 IgM-specific and IgG cross-reactive immunodominant epitopes, respectively. In addition to the antibody responses, T cells have important functions in immune protection against viral diseases. Hence the final objective was to examine the T cell responses in enterovirus infection. Peripheral blood mononuclear cells collected from HFMD patients were stimulated with EV-A71, and T-cell markers and cytokines were analysed by flow cytometry. EV-A71-infected and coxsackievirus A6 (CV-A6)-infected patients showed similar T cell responses suggesting that the induced T-cell responses were cross-reactive. A higher frequency of IFN-γ expressing CD4+ T cells was observed in children, but a higher frequency of IFN-γ expressing CD8+ T cells was observed in adults. This may be because CD4+ cells are involved in responses to primary infections, which mostly occur in children, while the CD8+ responses in adults represent immune memory. Cytolytic enzymes such as granzyme B and perforin, which are critical mediators for anti-viral immunity, were expressed in both children and adults. Higher granzyme B compared to perforin was expressed in CD8+ T cells in both children and adults, suggesting that a proportion of EV-A71-specific CD8+ T cells may not be directly cytotoxic. Similar expression of CD57+ CD8+ T cells was observed in children and adults. The expression of CD57 cells suggests that immunosenescence common in chronic infection may also play a role in EV-A71 T-cell immunity. Overall, this study provides new knowledge in the immunoprotection mechanisms against EV-A71